Stochastic modelling of abrasive waterjet controlled-depth machining - Lozano Torrubia, Pablo (2016)
Abrasive micro-waterjet processing is a non-conventional machining method that can be used to manufacture complex shapes in difficult-to-cut materials. The constant development of new materials with enhanced properties has sparked the interest in alternative machining technologies. Among these non-conventional machining methods, Abrasive Waterjet Machining is regarded as a flexible technology with potential to cope with a wide range of materials and applications. The use of a soft tool (i.e. the jet) is very advantageous because it makes it possible to perform different operations without modifying the equipment. However, this advantage poses a significant challenge: the erosion power of the jet is controlled through a set of operating parameters, and it is therefore necessary to have a deep understanding of the relation between such parameters and the effect of the jet on the surface. The process itself is subject to strong random variations, and this makes it even more complex to develop a detailed understanding of the optimum strategies to control the jet.